2013
DOI: 10.1074/jbc.m113.485896
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of α-1,4-Glucan Lyase, a Unique Glycoside Hydrolase Family Member with a Novel Catalytic Mechanism

Abstract: Background: ␣-1,4-Glucan lyase (GLase) is a glycoside hydrolase family member that degrades starch via an elimination reaction. Results: Crystal structures of GLase with covalently bound inhibitors show that the catalytic nucleophile can abstract the proton. Conclusion:The nucleophile has a dual function, acting successively as nucleophile and base. Significance: A single substitution converts a glycoside hydrolase into a lyase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…20 The crystal structure and the active pocket are shown in Fig. 20 The crystal structure and the active pocket are shown in Fig.…”
Section: Computational Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…20 The crystal structure and the active pocket are shown in Fig. 20 The crystal structure and the active pocket are shown in Fig.…”
Section: Computational Modelmentioning
confidence: 99%
“…Since no water molecule takes part in the reaction and the product 1,5-anhydrofructose is clearly different from those of other glycosidases, GLases form the subgroup 2 of GH31. [17][18][19][20] The formation of the covalent glycosyl-enzyme intermediate has been observed by trapping with 5-uoro-b-L-idopyranosyl uoride, and subsequent detection and sequencing of the labeled peptide by mass spectrometry. Previous experimental studies by kinetic isotope effects have suggested that the GLasescatalyzed reaction follows a two-step mechanism which involves both the glycosylation and deglycosylation steps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the H-2 is acidified during bond cleavage via the formation of cation character at C-1 and may then be abstracted by the catalytic base. Structural data show the catalytic nucleophile positioned over H-2 in structures of the covalent intermediate, implying that the role of the catalytic base is fulfilled by the nucleophile itself (Rozeboom et al, 2013).…”
Section: A-glucan Lyasesmentioning
confidence: 99%